A Theory of Gender Discrimination Based on the Household - Patrick Francois (Queen's University, Department of Economics, 1996)
This paper presents a new theory of gender discrimination in competitive labour markets which does not rely on any inherent gender asymmetries. Women and men are organized into households with each having identical household specific human capital. When labour market characteristics (effort, wages) differ, the possibility of mutually beneficial within household trades arises. Discrimination involves occupational segregation with men obtaining high paying efficiency wage jobs and women in piece rate work. It is shown that there always exists a Nash equilibrium in which firms benefit from discrimination by allocating high paying jobs exclusively to men, provided other firms also do so, as this ensures their employees (men) enjoy the benefits of within household trade and will satisfy incentive compatibility at a lower wage. A firm attempting to hire women in efficiency wage jobs makes strictly lower expected profits, since the predominance of men in the labour market means women are less likely to enjoy the benefits of within household trade and more likely to shirk. The model thus provides an intuitive explanation for discrimination in competitive labour markets even when the sexes are completely identical. It also suggests a positive role for affirmative action policies in moving the economy from the discrimination to a non-discrimination equilibrium.
Keywords: J71; J41; J16; 330; gender discrimination; efficiency wages; household models